Laboratory colonization of the European invasive mosquito Aedes (Finlaya) koreicus. Issue 1 (December 2017) - Ciocchetta, Silvia; Darbro, Jonathan; Frentiu, Francesca; Montarsi, Fabrizio; Capelli, Gioia; Aaskov, John; Devine, Gregor
Abstract Background Aedes (Finlaya )koreicus (Edwards) is a mosquito that has recently entered Europe from Asia. This species is considered a potential threat to newly colonized territories, but little is known about its capacity to transmit pathogens or ability to compete with native mosquito species. The establishment of a laboratory colony is a necessary first step for further laboratory studies on the biology, ecology and vector competence ofAe. koreicus . Results A self-mating colony was established at QIMR Berghofer Medical Research Institute (Brisbane, Australia) from eggs of the F1 progeny of individuals collected as free-living larvae in northeastern Italy (Belluno province). Mosquitoes are currently maintained on both defibrinated sheep blood provided via an artificial membrane system and human blood from volunteers. Larvae are maintained in rain water and fed with Tetramin® fish food (©2015 Spectrum Brands - Pet, Home and Garden Division, Tetra-Fish). Morphometric measurements related to body size were taken and a fecundity index, based on wing length, was calculated. An in vivo technique for differentiating male and female pupae has been optimized. Our findings provide the basis for further studies on the ecology and physiology ofAe. koreicus . Conclusion We describe the establishment of anAe. koreicus colony in the laboratory and identify critical requirements for the maintenance of this mosquito species under artificial conditions. The laboratory colony will facilitate studies investigating the vector potential of this species for human pathogens.